Методология научного познания: эмерджентный научно-педагогический кластер университетского образования - Буряк, В.В.; Шостка, В.И. (Культура народов Причерноморья, 2014)
История и методология науки – важнейшая сфера современного университетского
образования. В настоящее время в обществе большое внимание уделяется не только различным
отраслям науки, но и наукоемким технологиям, энергетике, экологии и др. В связи с этим методология
науки имеет характерные особенности в контексте общеобразовательных вузовских дисциплин.
Данная работа рассматривается в плане интеграции философии и методологии науки с другими
сферами науки и общественной жизни. Анализируются сложный образ современной науки во всем
многообразии, а также основные проблемы, возникающие в ходе научных исследований. В работе
систематизированы наиболее важные направления современных междисциплинарных
методологических подходов. Icторiя та методологiя науки – найважливiша сфера сучасноi унiверситетськоi освiти.
Зараз в суспiльствi велику увагу придiляють не тiльки рiзним отраслям науки, але й наукоэмним
технологiям, енергетицi, екологii та iнш. Методологiя науки маэ характернi особливостi в контекстi
освiтнiх дисциплiн. Робота розглядаэться в планi iнтеграцii фiлософii та методологii науки з iншими
науками та сферами суспiльного життя. Аналiзуэться складне зображення сучасноi науки, ii основнi
проблеми , якi виникають в процесi наукових дослiджень. В роботi систематозовано найважливiшi
напрямки сучасних мiждисциплiнарних методологiчних пiдходiв. History and methodology of science is most important sphere of contemporary university education.
At present in the society considerable attention is paid not only to different fields of science - intensive
technologies, power engineering, ecology and others. The methodology of science has characteristic properties
in the context of educational disciplines. This work is examined in the plan of the integration of philosophy and
methodology of science with other sciences and spheres of public life. Are analyzed the complex means of
contemporary science in entire its variety, and also the basic problems which appear before the scientists in the
course of scientific studies. In this work the most important directions of contemporary interdisciplinary
methodological approaches are systematized. In the second half of the twentieth century under the influence of
social, economic and technological factors, the situation in the world's education system is steadily beginning to
change. Reason for change in a fundamental shift in contemporary socio-cultural system of values of the
industrial age to a post. Development of modern civilization due to the exponential growth of scientific and
technological knowledge. Growing conflict between traditional and innovative forms of university pedagogy.
Intensively used educational practices based on globalized networked information resources. In university
education formed a research and teaching cluster encompassing perspective of philosophy of science, history of
science and methodology of science. Philosophical problems associated with the formation of academic science,
become relevant and priorities in the field of construction of modern university education. The methodology and
the history of science must be mentioned as a master for all special education courses is required for the
integration of cognitive practices in the scientific sphere. Assumed convergence of diverse cognitive approaches.
Object-oriented complex cognitive strategies are needed to accelerate the implementation of the programs of
interdisciplinary academic projects.